Promoting Social Innovation Projects with an Online Course: Creating Global Solutions for Sustainability - Calvo, Sara; Morales, Andrés; Castanho, Rui Alexandre; Santos, Eleonora (Smart Innovation, Systems and Technologies, 2023)
Social innovation is the process by which new ways of doing things are created to respond to the needs of society. This can be technological, for example embracing online or open-source technology, or it can be social, fostering local entrepreneurship. The objective of this chapter is to explore social innovation initiatives that have been carried out because of an online course created in FutureLearn. This study aims to provide the reader with an idea of ​​the relevance of social innovation to create global solutions. This study included a mixed methods approach; a FutureLearn dataset, a feedback questionnaire, and semi-structured interviews with learners. The MOOC was reported to provide confidence for those starting Social Innovation related initiatives. The findings confirmed that some learners have used the course to grow or scale their existing projects. It also confirmed that learners had been sharing the learning with a wide range of other projects and individuals. This demonstrates a way of scaling up social innovation knowledge, ideas and projects that would never be possible with other face to face or online conventional courses. This research offers insight into the development of sustainable social innovation initiatives and how educational technology facilitates and enhance these processes. This study will be of interest to researchers, academics, and students in the fields of social innovation, education, and sustainability.
Keywords: Latin America; online course; social innovation; sustainability; Scopus(2); WOS(2)